2012
DOI: 10.1093/mutage/ges023
|View full text |Cite
|
Sign up to set email alerts
|

Borneol administration protects primary rat hepatocytes against exogenous oxidative DNA damage

Abstract: Experimental evidences suggest that most essential oils possess a wide range of biological and pharmacological activities that may protect tissues against oxidative damage. In this study, we investigated DNA-protective effect of borneol, a component of many essential oils, against oxidative DNA damage induced in primary cultures of rat hepatocytes. Borneol was added to drinking water of Sprague-Dawley rats and DNA resistance against oxidative agents was compared in hepatocytes originated from control and borne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…It is well known that administration of natural products can suppress increased level of intracellular ROS [60]. Also our previous studies reported that natural extracts administration protects cells against exogenous oxidative damage, improves antioxidant status of cells or affects biochemical serum parameters [61][62][63]. In the current study pretreatment with lavender oil showed its preventive effects against oxidant-induced DNA damage in HepG2 cells.…”
Section: Discussionsupporting
confidence: 53%
“…It is well known that administration of natural products can suppress increased level of intracellular ROS [60]. Also our previous studies reported that natural extracts administration protects cells against exogenous oxidative damage, improves antioxidant status of cells or affects biochemical serum parameters [61][62][63]. In the current study pretreatment with lavender oil showed its preventive effects against oxidant-induced DNA damage in HepG2 cells.…”
Section: Discussionsupporting
confidence: 53%
“…Our findings are consistent with previous studies reporting that borneol may have anti-inflammatory [35], neuroprotective [36,37], and anti-oxidative DNA damage [38] effects. It has been suggested that because of borneol's ability to open and cross the blood-brain barrier over the hippocampus and hypothalamus regions, which are the areas of the brain that are most affected by central nervous system (CNS) disorders, borneol can assist the permeation of drugs that target the brain [39,40].…”
Section: Intranasal Herbal Formula Improved Communication Ability In supporting
confidence: 93%
“…These results suggest that carvacrol could afford a significant hepatoprotective and antioxidant effect against D-GalN -induced rats. After 7 day administration of borneol (17 or 34 mg/kg) in drinking water of rats concentration-dependant increase of total GSH in isolated hepatocytes was detected [83]. The stimulation of endogenous antioxidant defence systems -glutathione and related enzymes -by many plant compounds is a well-known phenomenon.…”
Section: Mutagenicity Anti-mutagenicity and Dna-protective Effectsmentioning
confidence: 99%